Analisis Intensitas Penggunaan Media Sosial terhadap Perilaku Impulsive Buying Mahasiswa STIE Eka Prasetya dalam Berbelanja Online - Sia, Wilbert; Angeline, Shenny; Ryu; Situmorang, Irvan Rolyesh (BUDGETING : Journal of Business, Management and Accounting, 2025)
This study aims to analyze the intensity of social media usage on the impulsive buying behavior of STIE Eka Prasetya students in online shopping. Social media has increasingly become an effective promotional tool, exposing students to advertisements, discounts, and influencer recommendations. The findings indicate that high social media usage intensity is closely related to students’ tendency to make spontaneous purchases. Psychological factors such as fear of missing out (FOMO) and social influences from peers further reinforce this consumptive behavior. The impact can be seen in students’ financial management, which becomes less controlled. Therefore, digital and financial literacy are needed to help students manage impulsive buying behavior in the social media era.   Keywords: Impulsive Buying, Students, Online Shopping , Social Media